Infekcné komplikácie u pacientov s cirhózou pecene - Jarcuska, Peter; Veselíny, Eduard; Orolín, Martin; Takácová, Viktória; Hancová, Martina (Klinicka mikrobiologie a infekcni lekarstvi, 2004)
AIM OF THE STUDY: To assess the objective incidence of infectious complications in liver cirrhosis, to find out correlation among stage of liver cirrhosis, number of infectious complications and mortality in cirrhotic patients. PATIENTS AND METHODS: 93 patients with liver cirrhosis were hospitalized from June 1996 to November 1998 (age: 53,44 I 8,03 years, Child-Pugh score: 11,58 I 2,12). 6 patients were in class B, 87 in class C of Child-Pugh classification. Ascites was found in 81 patients, pleural effusion was found in 14 patients. Chest X-ray, examination of ascites and pleural efussion an urine culture were performed by admission, the other infections were actively screened after clinical signs. RESULTS: Spontaneous bacterial peritonitis was found in 17 patients (18,28 %), secondary bacterial peritonitis in 5 patients (5,38 %), spontaneous bacteremia in 3 patients (3,23 %), spontaneous bacterial pleuritis in 3 patients (3,23 %), bronchopneumonia and infections of respiratory tract in 22 patients (23,66 %), uro-infection in 69 patients (74,19 %) and the other kinds of infection in 14 patients (15,05 %). Mortality of patients correlates with stage of liver cirrhosis and number of infectious complications. CONCLUSION: Infections are common complications in hospitalized cirrhotics. Infectious complications are the most common cause of mortality of cirrhosis, patients with bronchopneumonia, secondary bacterial peritonitis or spontaneous bacterial pleuritis had bad prognosis. Early antibiotic treatment at the base of culture and sensitivity is an optimal therapeutic approach in cirrhotics with infections.
Keywords: Female; Bacterial Infections; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; Liver Cirrhosis; jaterní cirhóza; bakteriální infekce